Answer:
3, 6, 9, 12, 15, 18, 21, 24, 27, 30, 33, 36, 39, 42, 45
Step-by-step explanation:
Answer:
350
Step-by-step explanation:
You can do this just believe in your self
It A
Hello!
We can solve this by using substitution
we can plug y = x - 1 into the other equation
So 2x - 3( x - 1) = -1
We can distribute the -3 to (x - 1)
2x - 3x + 3 = -1
Combine like terms
-x + 3 = -1
Subtract 3 from both sides
-x = -4
Since x is negative we can multiply both sides by -1
x = 4
We can plug x into the first equation
y = (4) - 1
y = 3
The answers are x = 4 and y = 3
Hope this helps!